AH-04 Anatomical Characteristic of the Pelvic and Thigh Region Muscles of Javan Pangolin, Manis javanica - Chairun Nisa'; Singgih Pratiknyo Sundawa; Supratikno Supratikno; Danang Dwi Cahyadi (Media Veteriner, 2015)
Anatomical Characteristic of the Pelvic and Thigh Region Muscles of Javan Pangolin, Manis javanica